#### Answer

$\dfrac{2}{5}-\dfrac{7}{10}+\Big(-\dfrac{3}{2}\Big)=-\dfrac{9}{5}$

#### Work Step by Step

$\dfrac{2}{5}-\dfrac{7}{10}+\Big(-\dfrac{3}{2}\Big)$
First, evaluate the subtraction $\dfrac{2}{5}-\dfrac{7}{10}$:
$\dfrac{2}{5}-\dfrac{7}{10}+\Big(-\dfrac{3}{2}\Big)=\dfrac{4-7}{10}+\Big(-\dfrac{3}{2}\Big)=-\dfrac{3}{10}+\Big(-\dfrac{3}{2}\Big)=...$
Take out common factor $-1$:
$...=-\Big(\dfrac{3}{10}+\dfrac{3}{2}\Big)=...$
Evaluate the sum inside the parentheses and simplify:
$...=-\Big(\dfrac{3+15}{10}\Big)=-\Big(\dfrac{18}{10}\Big)=-\dfrac{9}{5}$